Cooperativity of silanol defect chemistry in zeolites. Issue 1 (8th December 2022) - Chen, Ya-Fan; Schroeder, Christian; Lew, Christopher M.; Zones, Stacey I.; Koller, Hubert; Sierka, Marek
Abstract : Condensation reactions in silanol nests create strain in the structure of zeolite SSZ-55. A sufficiently high defect concentration allows the formation of 3-rings due to cooperative relaxation of the framework. Abstract : Deboronation treatment of zeolite B-SSZ-55 can generate vacancy defects consisting of four silanol groups (silanol nests). However, 1 H solid-state NMR spectroscopy indicates the prevalence of two silanol groups (silanol dyads) instead of four silanol groups. Such silanol dyads must be formed by the silanol condensation of two silanol groups at the silanol nests. Yet, the exact mechanism of this condensation and detailed structure of the silanol defect are not known. Here, the structure and formation mechanism of silanol dyads in the SSZ-55 zeolite have been investigated by both cluster and periodic density functional theory calculations. The calculated 1 H NMR chemical shifts agree with the experimental values, showing that the silanol dyads are indeed commonly present at the vacancies and the vacancy density plays a role in the relaxation of the zeolite framework. The nature (size) of the silanol clusters influences their acidity.